A novel role for EXP2 in invasion by Plasmodium sporozoites - Mello-Vieira, Joao (2022)
Plasmodium parasites, the causative agents of malaria, possess a translocon that exports parasite proteins into the infected erythrocyte, beyond the confines of the parasite. The parasite pore-forming protein Exported Protein 2 (EXP2) is a component of this translocon and the pore through which proteins are exported. Although EXP2, and other translocon components, are also expressed during the mosquito and liver stages of infection, their function remains unexplored. To study the function of EXP2 during the liver stage of infection, we used a genetically engineered Plasmodium berghei parasite line, generated by our collaborators. In this parasite line, the EXP2 gene is silenced during the mosquito stage, as the 3’ untranslated region of the EXP2 gene is excised, generating EXP2 knock-out sporozoites. The sporozoite is the mosquito transmissible form of the parasite, that when deposited in the mammalian host, infects the liver, giving rise to the pre-erythrocytic stage of Plasmodium infection. Using this transgenic parasite line, we observed that invasion of the hepatocyte by EXP2 conditional knock-out parasites is impaired, both in C57Bl/6J mice and in the hepatoma cell line HepG2, suggesting that invasion is dependent on EXP2. Using a combination of fluorescence and electron microscopy techniques, we show that EXP2 is present in the hepatocyte-infectious sporozoite in vesicles, in the apical end of the parasite. These vesicles are important for the invasion process, as they are discharged by the sporozoite and contain proteins important for hepatocyte adhesion and entry in the host cell. Stimulating sporozoites with conditions that mimic the host cell milieu, we observed that EXP2 relocates to the surface of the mosquito-transmitted sporozoite and that it is secreted by the sporozoite. We also observed that invasion defect of the EXP2 conditional knock-out parasites can be rescued by the exogenous administration of recombinant EXP2 or recombinant α-hemolysin, another pore-forming protein, suggesting that the function of EXP2 is through its pore-forming ability on the membrane of the hepatocyte. Invasion of cells via pores has been documented for a variety of intracellular pathogens, like Trypanossoma cruzi, Listeria monocytogenes and adenovirus. Importantly, the pore does not allow the parasite to cross the membrane, rather it induces changes in the host cell that make it endocytose the wounded region of the membrane. We observed that recombinant EXP2 can recapitulate the major hallmarks of the membrane repair pathway. On one hand, treating cells with recombinant EXP2 leads to influx of calcium to HepG2 cells. Moreover, invasion of Plasmodium berghei sporozoites is dependent of acid Sphingomyelinase and finally, the invasion defect of the EXP2 conditional knock-out sporozoites can be rescued by exogenously adding acid sphingomyelinase. This suggest that indeed EXP2 induces hepatocyte membrane repair, which plays a key role in parasite invasion. Overall, while our data show that Plasmodium parasites uses EXP2 for divergent functions in its life cycle, it also highlights the convergent evolution of different intracellular pathogens, which have developed similar strategies to take advantage of cellular responses to membrane damage, hitchhiking their way into the host cell.